An analysis of National Football League coaching trees and the network they comprise - McCullick, B. A.; Elliott, J.; Schempp, P. G. (International Journal of Sports Science & Coaching, 2016)
The purpose of this study was to analyze professional football coaches` coaching trees and the network they comprise. Employment histories were collected for head coaches (HCs) in the National Football League (NFL) along with the NFL HCs under whom they served as assistant coaches (ACs) prior to their first NFL HC position and repeated until no new mentors were found. Coaches` win-loss records, championships, and Pro Football Hall of Fame status were obtained. Three themes emerged from data analysis: (a) "Roots are a Must, But Fewer are Stronger"; (b) "Established Roots Prosper and Flourish"; and (c) "Prolific Bounties are Not Necessarily Successful Ones". Analysis revealed: (a) a limited number of apprenticeships appeared to be the best way to achieve HC success; (b) AC apprenticeships are best served under successful HCs; and (c) the weight attributed to an AC`s experience working under a successful HC should be viewed cautiously.